PENGARUH PENGGUNAAN MODEL BLENDED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV DI SDN 031 PELESIRAN BANDUNG - Darda Abdullah Sjam; Rina Indriani; Serra Indriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
In the learning process, students who are seen as lacking and learning achievement of students are still low is the backgrounds in this study. There must be a process of reciprocal interaction between teachers and students, or students with other students. This study aims to determine the effect use of blended learning models on the learning achievement of fourth-grade students at Elementary School number 031 Pelesiran Bandung. This study used a quantitative approach with a research design that used a quasi-experimental (Quasi Experimental Design). The sample of this study was class IV B, which consisted of 22 students as the experimental class and class IV A, which amounted to 22 students as the control class. This study used the instrument of the initial and the final test in the form of multiple choice questions. The data analysis technique used in this research is a t-test. The post-test value data from the experimental and control classes were then tested for hypotheses using the independent sample t-test formula to determine the effect of the blended learning model on student learning achievement. The results of calculations using the independent sample t-test formula showed that the t-count value is 3,012│> 2,079 t table and has a Sig value of 0.004 (Sig. > 0.05). It can be concluded that there is a significant effect on the post-test scores of students' learning achievement in the experimental and the control classes. The results of calculations using the effect size test show that the final value is 0.991. This means that from the two tests that have been carried out, there is a positive and significant influence on the blended learning model on student learning achievement in theme 9 of the richness of my country, sub-theme 3 preservation of natural resource wealth in Indonesia in class IV at Elementary School number 031 Pelesiran Bandung.